The Role of Physical Exercise in Improving College Students' Psychological Quality Under the Background of Ideological and Political Education - Bingbing Liu; Lei Zhang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Objective: Sports activities constitute a significant component of campus culture, embodying both cultural and spiritual dimensions. They wield a subtle yet profound influence on the holistic development of college students, encompassing physical well-being, mental health, and personality cultivation. Enhancing the construction of campus sports culture holds considerable merit in consolidating the primacy of ideological and political education within higher education institutions, augmenting the efficacy of physical education programs, and fostering the development of campus spiritual ethos. Accordingly, this paper endeavours to investigate the role of physical exercise in enhancing the psychological well-being of college students within the contextual framework of ideological and political education. Methodology: For this study, a random sampling method was employed to select 500 college students from two distinct universities. The participants, aged between 17 to 23 years, comprised predominantly (98.65%) Han nationality individuals, with 63.26% originating from urban or rural areas, and 54.68% being only children. The physical exercise, psychological stress levels, and health statuses of 405 college students were assessed utilizing standardized tools including the Physical Activity Memory Scale, the Chinese College Student Psychological Stress Scale, and the Disease Severity Scale. The categorization of physical exercise levels was determined by converting the assessment results of the Physical Activity Memory Scale into metabolic equivalents. Findings: Prior to conducting follow-up data analysis, the researcher administered diagnostic interviews to all participants, adhering to the criteria outlined in the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV). Subsequently, 36 students potentially exhibiting mental disorders, such as severe depression, anxiety, or obsessive-compulsive disorder, were excluded. Additionally, 43 individuals were unable to provide data due to reasons such as enrolment or dropout, while 16 participants failed to furnish data for other unspecified reasons. Consequently, the final sample comprised 405 individuals, consisting of 284 males and 121 females, with an average age of (19.04 ± 1.31) years. At baseline, a notable positive correlation was observed between disease status and psychological stress (r=0.26, P<0.05). Conversely, no significant correlations were found between physical exercise and disease status (r=0.06, P>0.01) or between physical exercise and psychological stress (r=-0.04, P>0.01). A multi-layer linear model analysis revealed that both psychological stress (β= 0.23, P<0.01) and physical exercise (β= 1.54, P<0.01) significantly predicted disease occurrence. Furthermore, the interaction between physical exercise level and psychological stress demonstrated significance (β= 0.05, P<0.05). Implications and Conclusion: Physical exercise serves as a modulating factor in the relationship between psychological stress and disease onset, potentially mitigating the adverse impact of psychological stress on health outcomes. Furthermore, engagement in physical activity has been associated with enhancements in mental well-being and resilience, suggesting potential benefits through the integration of physical activity into holistic educational approaches.